BIOASSAY-ASSISTED IDENTIFICATION OF PHORBOL ESTER FROM JATROPHA CURCAS (LINN.) TISSUE CULTURE - DEMISSIE A.G; LELE S.S. (International Journal of Pharma and Bio Sciences, 2010)
The study reported bio-assay assisted isolation of phorbol ester in optimized solid and liquid system tissue culture. The effect of the compound on human leukemic cell line (Jurkat J6) was conformed using MTT and SRB assays. The extract was analyzed using HPTLC in standard phorbol 12- myristate 13-acetate equivalent. Phorbol ester composition in seed oil was found to be 1.78 + 0.34%. The composition from callus and suspension cultures sources was 0.145 + 0.11% and 0.173 + 0.15% respectively. The HPTLC profile of isolated PMA found to be Rf= 0.38 + 0.02. The biological activity of phorbol ester was observed significantly proliferate the human leukemia cell line (Jurkat J6) even at 5μg/ml. This result provides the evidence that phorbol ester can be produced through plant cell In vitro. Thus, this bioassay-guided method to identify phorbol ester is reliable and reproducible for further bioprocess, biopharmaceutics and biotechnological studies.